Identification of Role Ambiguity and Role Conflict Job Stress Among Nurses in Cardiac Surgical Intensive Care Units in Baghdad City - Bayda’a Abdul Kareem, (Iraqi National Journal of Nursing Specialties, 2023)
Objecthe: The study aimed to determine the level and sources of stress related to the role ambiguityand role conflict which stress experienced by the nurses, who were in intensive care units, andto find out relationship between role ambiguity and role conflict stress anc some variables such as (age,gender, educational level, marital status, and years of experience in cardiac surgical intensivecare unit).Methodology: ٨ descriptive-analytic Study was conducted on cardiac surgical intensive care unitsnurses in Baghdad hospitals. The sample of the study were selected purposively and consisted of 60nurses who were working in cardiac surgical intensive care units in Baghdad city (Ibn Al- BitarHospital for Cardiac Surgery, Ibn Al-Nafis Hospital for Cardiovascular Diseases, and the Iraqi Centerfor Heart Diseases) in the period of 1st February 006 to the 9th April 2006.٨ Questionnaire was designed to consisted of two parts, first part concerned with the demographiccharacteristics of sample and the second part concerned with the role ambiguity and role conflictenvironmental stressors, and it contain 20 items describing the Role ambiguity and role conflictstressors.Results: The results of the study revealed that the most of sample were females, their age ranged from(30-39) years, most of them were university graduation, single, with (6-10) years duration working incardiac surgical intensive care units. Also the results revealed that nurses in cardiac surgical intensivecare units suffers from moderate level of stress related to the role ambiguity and role conflict related toenvironmental stressors RS: (64.44).Recommendations: It is recommended that stress management programs should be employed to assistcardiac surgical intensive care units nurses to deal with job stress which resulting from role ambiguityand role conflict, and found out the ways to limitation, and clarification her roles at work and givethem opportunity for training to deal with new challenge.